Music business in Zimbabwe in the backdrop of music piracy in the 21st Century - Muranda, Richard (Africa Institute for Culture, Peace, Dialogue & Tolerance Studies, 2022)
Music Business in Zimbabwe in the Backdrop of Music Piracy in the 21st Century. In Driving Socio-economic Development Through Value Addition and sustainable use of Resources: Challenges and Prospects (p.229-244). Edited by H.T. Ngoshi & V.Z. Nyawo. Africa Institute for Culture, Peace, Dialogue & Tolerance Studies: Harare.